Students’ Awareness, Acceptance, and Attitude Towards the Implementation of Green TVET - Zawawi, Muhammad Amirul Haziq; Lai Chee Sern, (Online Journal for TVET Practitioners, 2024)
Current technical and vocational education and training (TVET) increasingly focus on the development of skills and knowledge related to sustainable practices and green jobs. However, the implementation of green TVET is not comprehensive due to our country's education system, which lacks emphasis on sustainability and environmental challenges. This results in students lacking sufficient knowledge about the involved issues. In light of this, this study is conducted to determine and identify the level of awareness, acceptance, and attitudes of TVET students toward the implementation of Green TVET programs. The study adopts a quantitative approach with a survey design through a questionnaire. Using random sampling method, a total of 165 undergraduate students in the field of education at the Faculty of Education and Vocational Technology, UTHM, participated as respondents. Descriptive analysis, including mean and standard deviation, as well as independent t-test, were employed to analyze the data. The study findings indicate high minimum scores for the aspects of awareness, acceptance, and attitudes of TVET students toward the implementation of Green TVET. The study also found no significant differences between male and female students in terms of awareness and acceptance, while for attitudes, there was a significant difference between male and female students. In conclusion, this study provides a more in-depth insight into the level of awareness, acceptance, and attitudes of students, contributing to a better understanding of how Green TVET is perceived and embraced by students.